Análisis del proceso de comunicación con clientes mediante la aplicación de campañas publicitarias (2011)
The document aims to formulate a basic design of a process of communication between organizations and their customers in order to determine the motivating factors of consumption and use them to achieve maintenance of customers in the short term also points to the design of a recognition of the communication process with customers' organizations so that they can examine their motives for consumption (material or concepts) and other aspects that can make this a process that delivers value to the relationship between companies and customers, through the use of literature and inquiry into advertising and marketing agencies on the design of relational marketing campaigns and loyalty.